Development of a method for quantitative determination of nitric oxide (NO) in rat tissues based on high-performance liquid chromatography and mass spectrometry - N. S. Popov; D. A. Gavrilenko; M. S. Baranov; V. Yu. Balabanyan (Фармация и фармакология (Пятигорск), 2024)
A quantitative assessment of nitric oxide (NO) production in body tissues is an urgent problem in pharmacology and biochemistry. The study of physiological processes occurring with the participation of NO, as well as the metabolism and pharmacodynamics of pharmacological agents from the group of NO donors, requires the introduction of accurate and reproducible methods for the quantitative determination of this metabolite in biological media.The aim of the study was to develop the HPLC-MS/MS methods for the quantitative determination of NO in various tissues of rats.Materials and methods. The indirect NO quantification was based on estimation of the level of more stable metabolites: nitrites and nitrates extracted from rat tissues by homogenization with water. The reduction of nitrates to nitrites was carried out using nitrate reductase. The derivatization of nitrites was based on a reaction with Griess reagent. The resulting azo dye was determined by HPLC-MS/MS using an Agilent InfinityLab Poroshell 120 EC-C18 4.6×100 mm, 2.7 μm analytical column. The total chromatographic analysis time was 12 minutes, and the analyte retention time was 6.1 minutes. The analytical range of the method was 0.1–100.0 nmol (in terms of nitrite) per 1 ml of plasma or tissue homogenate.Results. The developed a bioanalytical method was validated according to the following parameters: a selectivity, a matrix effect, a recovery degree, a sample transfer, an analytical range linearity, a lower limit of quantification (LLOQ), an intra- and inter-assay accuracy and precision, and a stability at all the stages of the analysis. To test the method, the NO content in the plasma, brain, heart, aorta and lungs of rats was determined.Conclusion. The developed bioanalytical HPLC-MS/MS methods fully meets the validation requirements. The metrological characteristics of the technique make it possible to highly accurately estimate the NO production in various tissues of rats, which is undoubtedly relevant and in demand in the study of pathological processes as well as the mechanism of action of pharmacological agents from the group of NO donors.